Chronic Pelvic Pain Syndrome among women - challenge in diagnostics and management. Current literature review - Zielińska, Zuzanna; Nowak, Karolina; Olejarz, Zuzanna; Drygała, Zuzanna; Wyrwał, Julia; Słowik, Magdalena; Nowak, Karolina; Nieć, Maria; Gierlach , Katarzyna; Krasuska, Martyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Chronic Pelvic Pain Syndrome (CPPS) is characterized as intermittent or constant pain located in the lower abdomen or pelvis, persisting continuously for at least 6 months [1]. Reports on the prevalence of chronic pelvic pain indicate the occurrence of this condition at a level of 5.7–26.6% in women of reproductive age. However, only a third of women suffering from chronic pelvic pain, seek medical care [2]. Clinical picture of CPPS consists of various patterns and symptoms, often as the intersection of the multiple systems, which additionally complicates and delays the diagnostic process. The aim of this review is to summarize existing literature about the diagnostics and management of Chronic Pelvic Pain Syndrome among women and create an awareness about the challenges which this condition poses for healthcare professionals. A brief description of the state of knowledge: Chronic Pelvic Pain Syndrome is a multifaceted condition and the pathophysiology of it has not yet been comprehensively studied. Clinical picture often involves dysfunctions in pelvic floor, urinary tract, or gastrointestinal system. Treatment involves a multidisciplinary approach including non-pharmacological and pharmacological interventions. Summary (conclusions): Chronic Pelvic Pain is a complex condition involving symptoms affecting the psychological, gastrointestinal, musculoskeletal systems. The most successful treatment approach emphasizes the role of collaboration among a diverse team of specialists such as gynecologists, gastroenterologists, psychiatrists, psychologists, and physiotherapists. More research focused on multimodal strategies in management of the CPP is needed to match patients most effectively with the most suitable combination of treatment and reduce the systemic consequences of chronic pain.